The Feasibility of Live Streaming DW English As Reading Instructional Technology Media For ESP (Learner Perspective) - Muhammad Chairil Imran; Khaliq Bashar; Dwi Syukriady; Budiarti Putri Uleng (CV. Eureka Murakabi Abadi, 2023)
The use of technology in learning English-reading skills has grown rapidly. One such technology is the computer-aided learning media. The use of computer media in the field of education has many advantages as they are easier to access, disseminate and store. The aim of present study is to investigate the impact of computer assisted language learning (CALL) technology on Indonesian learners' reading skills. This study applied quantitative research. The results of study found that the use of information technology in learning is marked by the interaction between students and materials through internet technology, the existence of programmed teaching, and flexibility in the process for learning both in terms of time and place. It can be concluded that it is very possible for us to be easily literate through various media; with this we can improve the quality of reading.